BCOR Expression in Endometrial Stromal Sarcoma: A Single-Center Study - Nasir, Hira; Atiq, Aribah; Bashir, Azra; Chughtai, Akhtar Sohail; Chughtai, Omar; Khan, Faria Waqar (Biological and Clinical Sciences Research Journal, 2025)
Endometrial stromal sarcoma (ESS) is a rare uterine neoplasm of mesenchymal origin that requires careful subcategorization due to its distinct prognostic implications. Recent studies have identified BCOR (BCL6 corepressor) as a reliable immunohistochemical marker with potential diagnostic value in high-grade ESS, aiding differentiation from other uterine sarcomas. Objective: To evaluate the diagnostic utility of BCOR expression in endometrial stromal sarcomas and to highlight its role in distinguishing high-grade ESS as a unique pathological entity for targeted treatment strategies. Methods: This prospective single-center study included 30 histologically confirmed cases of endometrial stromal neoplasms. Cases with insufficient tissue for immunohistochemistry or missing paraffin blocks were excluded. Formalin-fixed, paraffin-embedded tissue samples were subjected to BCOR immunohistochemical staining, and nuclear expression in tumor cells was assessed. Statistical analysis was performed to determine the association between BCOR expression and histological subtype. Results: Nuclear BCOR expression was detected in 3 (10.0%) of the 30 endometrial stromal neoplasms. All positive cases corresponded exclusively to high-grade ESS. Among nine cases of high-grade ESS, 3 (33.3%) exhibited BCOR expression, demonstrating a significant association with this subtype (p = 0.005). No BCOR expression was observed in endometrial stromal nodules, low-grade ESS, or undifferentiated uterine sarcomas. Conclusion: BCOR expression is a specific marker for high-grade ESS, facilitating its distinction from low-grade ESS, stromal nodules, undifferentiated uterine sarcomas, and other uterine pathologies. Incorporating BCOR immunostaining in diagnostic protocols may enhance diagnostic precision and guide individualized therapeutic approaches.